Functional programming for Java (LiveLessons (Indianapolis, Ind.), 2018)
"Functional Programming for Java LiveLessons provides a solid foundation for designing and creating Java code using the functional programming style. Simon Roberts, best-selling author of Java Certification and programming books and video titles, has created a unique video course using live-action lectures, code demos, and whiteboard instructions to take learners on a learning journey by telling a story. Functional Programming for Java LiveLessons is a complete resource where each new concept is introduced gradually, based on examples that start in the familiar object-oriented style. A solid foundation is created before adding on more complicated concepts. The discussion then examines how this example might be improved and introduces functional concepts in small steps, building in relevant code as you go and in a way that emphasizes understanding. Exercises are suggested throughout, allowing the viewer to stop and try solving the examples on their own before continuing. The code for this course is available as a GIT repository and viewers are encouraged to work with it to further their understanding."--Resource description page